Manoel de Barros: confluência entre poesia e crônica - Rodrigues, Paulo Morgado (2007)
This research aims at the communicative and translation possibilities that result from journalistic chronicles and poetry. To do so, we have brought the poetic construction of some poems of Manoel de Barros as an attempt to locate the use of elements that are peculiar of the journalistic chronicle, as a case study. The methodology of this work is that of a bibliographic enquiry, in order to obtain data about the way in which Manoel makes poetry, and about the structure of journalistic chronicle. Strictly concerning the signic processes operated in Latin America, we also have studied the semiotic dynamics of culture. Starting from the theory of factor and language functions by Roman Jakobson, we have pointed out the differences between them, specially between the referential function (usually linked with chronicle), and the poetic function. On the other hand, we have visualized their possible relationships based on the text concept and on the semiotic notion of boarders by Iuri Lotman, and their permeability, which makes it possible to have exchanges, dialogues and hybridism between distinct texts. Authors such as Lezama Lima, Severo Sarduy, Serge Gruzinsky, Amálio Pinheiro and Haroldo de Campos help us to map cultural features of Latin América which intensify connections between texts and cultural series from several points of time/space. The Latin American cultural environment has been studied for its high relational dynamism and for its open and migrant complexity which generates new ways of communicative procedures. We have analyzed one of each of Manoel de Barros 18 books as theoretical corpus. The criterion used for the selection of the poems was to choose the ones that seemed to incorporate most chronicle elements. Finally, Manoel de Barros shows to be not only a very sensitive poet to his cultural context but also, and above all, as good a chronicler as a poet, in that chronicle and poetry supplement each other in his work